A TRANSLATION OF BORROWING WORDS IN STEPHENIE MEYER’ S ‘ECLIPSE’ INTO INDONESIA - Ira Miranti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2011)
The purpose of this study is describing translation using borrowing strategy in the novel Eclipse by Stephenie Meyer that is translated into Indonesia. Data in this research are quoted and classified based on the strategy which is used by the translator in translating from SL to RL using Borrowing strategy which is stated by Vinay and Darbelnet (2000:84) and Molina and Albir (2002:520). In this research, the writer finds the borrowing strategy which is used by the translator; use two techniques such as: (1) Naturalized Borrowing shows themodification of spelling and/or pronunciation (referred to EYD), (2) applying borrowing without intentionally modification (pure borrowing). Based on the research, the researcher found 330 data. It is concluded that the total number of pure borrowing (115 words/35%) and naturalized borrowing (215 words/65%).Keywords: Translation, Pure and Naturalized Borrowing